2022
DOI: 10.21203/rs.3.rs-1196107/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification And Evaluation of Reference Genes For Cynanchum Auriculatum Under Various Stress Conditions

Abstract: Baishouwu (Cynanchum auriculatum) is a kind of critical Chinese herbal medicine. However, compared with the studies of other Chinese herbal medicines, the screening study on the reference genes of C. auriculatum is still the blank. Deterioration of the natural environment severely affects the growth and development of C. auriculatum. This study screened and identified suitable reference genes of C. auriculatum under various stress conditions. Based on qRT-PCR, geNorm, NormFinder, BestKeeper, and RefFinder were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Relative expression levels were calculated using the 2 −ΔΔCT method ( Livak & Schmittgen, 2001 ). By screening four reference genes of Cynanchum auriculatum, we found that ACT7 was the most stable under different abiotic stresses and hormone treatments and that GAPDH was the most stable in different tissues, so we selected ACT7 and GAPDH as internal control ( Zhu et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Relative expression levels were calculated using the 2 −ΔΔCT method ( Livak & Schmittgen, 2001 ). By screening four reference genes of Cynanchum auriculatum, we found that ACT7 was the most stable under different abiotic stresses and hormone treatments and that GAPDH was the most stable in different tissues, so we selected ACT7 and GAPDH as internal control ( Zhu et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%